The economic–environment relation: can post-Keynesians, Régulationists and Polanyians offer insights? - Lynne Chester; Joy Paton (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
As the environmental debate has intensified, post-Keynesians, Régulationists and Polanyians remain relatively silent. All treat time as historical, consider economic issues subordinate to politics and have plenty to say about growth, institutions, uncertainty and path-dependent events. These concepts seem pertinent to understanding the economic–environment problematic. This article explores the 'environmental potential' of these three heterodox economic traditions. We examine the conception of nature underpinning each methodological approach and the ability of their key conceptual tools to explain the economic–environment relation. Methodological pluralism and a project driven by the neoclassical agenda, we posit, seriously weakens the possibility of a post-Keynesian-grounded coherent environmental perspective. On the other hand, the Régulationists and Polanyians provide cogent analytical frameworks to advance explanations of the economic–environment relation and the contemporary environmental challenge.
Keywords: B50; B52; Q50; 330; capitalism; environment; Polanyi; post-Keynesian; Régulation theory